ClockOME: searching for oscillatory genes in early vertebrate development - Liber, Marta (2021)
Embryo development is a dynamic process regulated in space and time. Cells must integrate biochemical and mechanical signals to generate fully functional organisms, where oscillatory gene expression plays a key role. The embryo molecular clock (EMC) is the best known genetic oscillator active in embryo segmentation, involving genes from the Notch, FGF, and WNT pathways. However, the list of cyclic genes is still incomplete mostly due to the challenges involved with studying periodic systems. Recently, such studies have become more feasible with the development of pseudo-time ordering algorithms that search for candidate oscillatory genes using large transcriptomics datasets sampled without explicit time measurements. This study aims at finding candidate oscillatory genes - ClockOME - active in early chick embryo development. Two Gallus gallus microarray transcriptomics datasets from Presomitic mesoderm (PSM), and one dataset from limb segmentation were gathered from GEO and ArrayExpress. To normalize these data from different experiments, an RData package - FrozenChicken - was developed to apply a frozen Robust MultiArray (fRMA) normalization to the data. Next the datasets were processed with Oscope (a pseudo-time ordering algorithm) to search for candidate periodic genes clustered by similar oscillatory behaviour. The clusters of predicted oscillators were then subject to functional enrichment and interaction network analyses to highlight the biological functions associated with these genes. Oscope predicted three clusters of oscillators: two in PSM (106 and 32 genes), and one in Limb (162 genes). Overall, the genes are associated with regulatory, morphological, and developmental processes. Mesp2, a gene involved with the EMC, was found in this dataset, validating the approach, however, the majority of genes are novel oscillatory candidates, associated with chromatin and transcriptional regulation, as well as protein and oxygen metabolism. The list of candidate oscillators represents a valuable resource for guided experimental validation to discover additional members of the chick EMC. Six genes have been proposed for high-priority experimental validation: SRC, PTCH1, NOTCH2, YAP1, KDR, CTR9.